Evaluasi Kebijakan Perda No. 4 Tahun 2013 Tentang Penanggulangan HIV/AIDS di Kota Surabaya (Kajian Terhadap KPA (Komisi Penanggulangan AIDS) dan data kasus HIV/AIDS tahun 2010 s/d 2014 di Kota Surabaya) - Dendy Guswantoro (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2014)
AIDS Commission (KPA) noted that the East Java city of Surabaya is still ranked first number of HIV AIDS in East Java. In connection with this, then in order to provide legal certainty and protection against any efforts to combat HIV and AIDS in Surabaya established Regulation No. 4 Year 2013 on HIV and AIDS. In this study used qualitative research methods and evaluation methods used